A Randomized Controlled Trial of a Healthy Lifestyle Intervention to Improve Mental Health among School-Going Adolescents - Esra Tajik; MohammadReza Mohammadi; Hamid Rahmanian (Iranian Journal of Psychiatry)
Objective: Despite growing evidence on the influence of lifestyle on adolescent mental health, structured educational interventions addressing multiple health dimensions remain limited. The objective of this study was to assess the effectiveness of a healthy lifestyle educational intervention in improving mental health results among secondary school students. Method: A randomized controlled trial based on the Information, Motivation, and Behavioral Skills (IMB) model was carried out with 347 adolescents (182 in the intervention group and 165 in the control group) from twelve secondary schools in Tehran. Participants completed a set of questionnaires assessing knowledge and attitudes concerning diet, physical activity, and stress management. Additionally, assessments included measures of eating behavior, daily physical activity, and psychological state using the Beck Depression Inventory-Short Form (BDI-S, BDI-13), and the Depression, Anxiety, and Stress Scale [DASS-21]). The innovation is addressing multiple dimensions of adolescent health in a comprehensive way and targeting mental health outcomes. It consisted of eleven one-hour sessions delivered to the intervention group in their schools. Data were then analyzed using descriptive statistics, Chi-square (association between categorical variables) and two-way repeated measure ANOVA (difference in the means score at follow-up). Results: In the intervention group, significant improvements were observed in knowledge about lifestyle factors, including diet, stress management and physical activity and, from baseline to post-intervention (P < 0.05). Attitudes toward stress management also showed significant positive changes. Behaviorally, there was an increase in physical activity, participation in relaxation activities, and eating breakfast, while unhealthy practices such as eating out, drinking sweetened beverages, and consuming fast food decreased (P < 0.05). Additionally, depression symptoms decreased by 1.9 points (mean ± SD) at the 6-month follow-up (P < 0.05). Conclusion: This study demonstrates that a six-month healthy lifestyle educational intervention can effectively enhance adolescents’ knowledge, attitudes, and behaviors related to healthy lifestyle factors, leading to improved mental health outcomes.